Utilization of Calcium Sources in the Saponification Process of Lemuru Fish Oil for Protected Fat Supplements - Marjuki, Marjuki; Hartutik, Hartutik; Huda, Asri Nurul; Oktafiyanti, Kamelia; Phusparini, Arum (Jurnal Sain Peternakan Indonesia, 2025)
This study evaluated the effectiveness of several calcium compounds in the saponification of lemuru fish (Sardinella lemuru) oil to produce protected fat supplements for ruminants. Four calcium sources—Ca (OH)₂, CaCO₃, CaCO₃·MgCO₃ (dolomite), and CaSO₄ (gypsum)—were tested using a completely randomized design with five replications. The parameters observed included product texture, proximate composition (moisture, ash, fat), fatty acid profile, and solubility under rumen-like (neutral) and gastric (acidic) conditions. Results indicated that Ca (OH)₂, CaCO₃·MgCO₃, and CaSO₄ were effective in forming calcium or mixed fatty acid salts, while CaCO₃ failed to bind free fatty acids. Among the effective compounds, Ca (OH)₂ produced the fastest hardening product, whereas dolomite and gypsum provided more balanced mineral contributions (Ca, Mg, and S). All protected fat products were less soluble in the rumen environment but readily decomposed under acidic gastric conditions, ensuring nutrient bypass. These findings suggest that low-cost and locally available calcium sources can be utilized to develop protected fat supplements that are both nutritionally safe and practical for ruminant feeding. Further research is needed to optimize the water-to-oil ratio and enzyme application for improved efficiency.